Students’ Attitudes Toward Physics and Its Influencing Factors: A Literature Review - Kurniawan, Aris; Kuswanto, Heru (Kasuari: Physics Education Journal (KPEJ), 2025)
This literature study aims to address factors that influence students' attitudes towards physics and variations in learning methods that can be a reference for teachers to enhance students' attitudes towards physics. This study used systematic literature review method. Literature review was conducted using the keyword "attitudes towards physics". These keywords are searched through the Scopus search engine. We found 38 articles relevant to keywords with publication time constraints being the previous ten years. By using  literature as a review, it was found that students' attitudes towards physics are influenced by a positive school environment, learning methods applied in the learning process, gender, type of school and age. We did not find that personality and grade level influenced students' attitudes towards physics as previous research concluded. In addition, we found more variety of learning methods to enhance students’ attitude towards physics. Variations of learning methods that are proven to significantly enhance students’ attitudes towards physics are problem based learning model, jigsaw cooperative learning model, inquiry learning model, STEM approach, peer instruction method, cognitively guided instruction method, multiple intelligences based instruction method, concept mapping, flipped classroom method, dialogical practical work, active learning, blended learning, augmented reality, game-based learning module, computer simulations, virtual laboratory, creating digital storytelling, and haptic augmented simulation.